CHEMICAL COMPOSITION PROFILE OF TAMBELO (Bactronophorus sp.) THAT LIVES IN RHIZOPHORA SP. IN SOUTHEAST SULAWESI COAST - Lely Okmawaty Anwar; Ary Tamtama; Maulidiyah -; Muhammad Nurdin (PROSIDING SEMINAR KIMIA, 2015)
Tambelo (Bactronophorus sp.) is a wood borer grouped into mollusc. Tambelo lives in died and decayed mangrove logs. Based on the empirical experiences of the coastal people of Southeast Sulawesi, it indicated that tambelo is rich in nutrition for humans health. Tambelo is highly perishable and it is rarely processed. Tambelo (Bactronophorus sp.) in Southeast Sulawesi coast lives in several kinds of mangroves. One of which is on Rhizophora sp. and has sweet and savory in taste. The objectives of this research were to get information about the chemicals composition, amino acids and fatty acids profile of tambelo. Proximate analysis was used to determine chemicals composition (water, protein, fat, carbohydrate, and ash). Metode HPLC was used to determine amino acid composition and composition of unsaturated fatty acids using Gas Chromatograph (GC). Quantitative datas was processed by simple statistical method (average and standard deviation). The data that have been processed was descriptively analyzed. The results of this research showed that the fresh tambelo has 82,51 % of total water content, 8,21 % of protein content, 3,34 % of fat content, 3,68 % of carbohydrat content (by different), and 2,27 % of ash content. The protein content of composed of 17 amino acid that consisted of 9 essential amino acids and 8 nonessential amino acids. The highest content of essential amino acid is leucina and the highest non essestial amino acid is glutamic acid. The highest content of unsaturated fatty acidc is oleic (MUFA) and linoleic (PUFA).